The legal regulation of business activity of Filiae Familias in the principate period (Actio de Peculio) - Ejankowska, Elżbieta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The application of actio de peculio due to filiae familias – in the principate period – is not an often discussed topic in literature. This claim was one of additional actions, the aim of which was 35 to include the family superiors and owners of slaves in the responsibility for contractual obligations. Not only in Gaius Institutions (G.4,69–4,77), but also in the formula of the claim of the reconstruction of the praetorian edict written by. O Lenel, no feminine persons are included. However, it arises from other sources that this action could have been applied due to business activity of daughters, which was performed on the basis of peculium. Actio de peculio – in reference to a married daughter being a subordinate of the father – also had another function; it was the equivalent of actio rerum amotarum.

Zastosowanie actio de peculio z powodu filiae familias w okresie pryncypatu nie jest zagadnieniem często poruszanym w literaturze przedmiotu. Skarga ta należała do powództw o charakterze dodatkowym, których celem było rozciągnięcie odpowiedzialności na zwierzchników familijnych i właścicieli niewolników za zobowiązania kontraktowe osób im podległych. Jakkolwiek zarówno w Instytucjach Gaiusa (G.4,69–4,77), jak i w formule skargi zamieszczonej w rekonstrukcji edyktu pretorskiego zredagowanego przez O. Lenela nie są wymienione osoby płci żeńskiej, z innych tekstów źródłowych wynika, że powództwo to mogło być stosowane ze względu na działalność gospodarczą, którą córki rodziny prowadziły w oparciu o peculium. Actio de peculio w odniesieniu do zamężnej córki podległej władzy ojcowskiej spełniała też inną rolę – była odpowiednikiem actio rerum amotarum.
Keywords: actio de peculio; daugther under patria potestas; peculio property; actio rerum amotarum; principate; complaint; praetorian law; córka podległa patria potestas; majątek pekuliarny; pryncypat; powództwo; prawo pretorskie